Persistent pit viper envenomation in three dogs. (August 2019) - Schaer, Michael
Abstract: Introduction: North Central Florida is the home to several venomous snakes. The most clinically significant pit vipers include the Eastern Diamondback Rattlesnake, the Water Moccasin, and less commonly the Timber Rattlesnake. Many of the dogs and cats that become envenomated by these particular snakes have moderate to severe clinical signs requiring the use of antivenom in doses that can range from 1 to 20 vials with the average case requiring two vials. Oftentimes, the pet owners' financial limitations restrict the amount of antivenom that can be administered initially to severely envenomed cases. Most of these patients will become clinically stable after the first 48 hours of treatment, but there are rare instances where some patients will follow this same initial course, and then revert back to the initial signs of envenomation associated with delayed absorption of redistributed venom from other tissue sites in addition to the bite site. This report describes three dogs that showed signs of persistent and/or recurrent envenomation requiring additional doses of antivenom. Methods: The medical records of three dogs showing signs of persistent envenomation were reviewed by the author who was available and provided assistance during the course of the dogs' respective hospitalizations. The dog's signalment, time of year of the envenomation, clinical signs, treatment, and outcome are provided in each case. Results: Each of these three dogs showed severe signs of envenomation characterized by marked mental depression, prostration, hemorrhagic lymphedema, and evidence of prolonged coagulation times. Initial treatment in each consisted of intravenous crystalloid solution and polyvalent crotalid antivenom that exceeded the usual average dose as reported in the literature. After the coagulation test normalized during the first three days, all of them reverted to abnormal prolonged clotting times with signs of clinical deterioration requiring additional doses of antivenom. Clinical stability was eventually reached and all dogs survived to be discharged. Conclusions: The clinical course of the three dogs described in this study showed that veterinary patients can experience persistent envenomation in a similar manner as described in humans. It behooves the veterinary practitioner to be aware of this complication and to be prepared to extend antivenom treatment as deemed necessary. Highlights: Three cases of persistent envenomation in dog. Clinical findings similar to those seen in man. Persistent envenomation requires increased doses of antivenom.